Finite element analysis of geotechnical problems using small strain model - Lim, Yee Heng. (2009)
This final year project (FYP) is concerned with the stiffness of soils at small strains and its implication in finite element analysis as implemented in Plaxis the Hardening Soil with small strain stiffness model (HS-Small). The strain range in which soils can be considered truly elastic, i.e. where they recover from applied straining almost completely, is very small. With increasing strain amplitude, soil stiffness decays non-linearly: Plotting soil stiffness against log(strain) yields characteristic S-shaped stiffness reduction curves. Also, at the minimum strain which can be reliably measured in classical laboratory test, i.e. triaxial and oedometer tests without special instrumentation, soil stiffness is often less than half its initial value. Thus, if this non-linear variation of soil stiffness at very small strains is considered in the analysis of soil-structure interaction, analysis results should improve considerably. The newly developed Plaxis Hardening Soil with Small Strain Stiffness (HS-Small) model is the upgrading of existing Hardening Soil model which takes into account the effects of small strain stiffness. Thus, the objective of this FYP is to understand how this Plaxis HS-Small Model works by considering the concepts of small strain stiffness, the new input parameters and the governing formulae. Besides, this FYP also compared the results of analysis using Plaxis Hardening Soil model and Plaxis HS-Small model involving hypothetical and real excavation problems. The HS-Small model produces smaller wall deflection, ground settlement and bending moment than those from the HS model. For soft clay, Both HS-Small and HS models produce similar results.